Effects of sepiolite and biochar on the photosynthetic and antioxidant systems of pakchoi under Cd and atrazine stress. Issue 11 (2nd November 2022) - Gao, Zhixin; Liu, Yetong; Huang, Qingqing; Li, Boyan; Ma, Tiantian; Qin, Xu; Zhao, Lijie; Sun, Yuebing; Xu, Yingming
Abstract: Sepiolite and biochar effectively immobilize Cd and atrazine in vegetable soils. This study further investigated the effects of sepiolite and biochar on the photosynthetic and antioxidative defence systems of pakchoi under Cd and atrazine stress. The results showed that after adding sepiolite and biochar to contaminated soil, the chlorophyll content was restored and the photosynthetic rate increased, whereas the soluble sugar content of pakchoi decreased. In the antioxidant system of the plants, the activities of peroxidase, ascorbate peroxidase, and superoxide dismutase decreased, while the activity of catalase increased. The content of malondialdehyde, glutathione, and O2 ·− increased, but the content of H2 O2 decreased. In general, remediation materials reduced the bioavailability of Cd and atrazine, reduced the stress on pakchoi, and restored and improved the rate of photosynthesis and function of antioxidants.